Place Branding: What Distinctiveness for the Southern Territories? An Analysis Through the Prism of a Moroccan Region - Moussalim, Sanaa (Journal of Applied Business and Economics, 2021)
Over the past 20 years, place branding has received increased attention, both as a practice and as a subject of academic studies. Its rapid expansion in territories can be explained by globalization and its corollary, the feeling of fierce competition between places to attract investment and visitors on the one hand, and the adoption by the public sector of private methods and tools, as part of the managerialist trend, on the other hand. Based on the results of research conducted in the Oriental region of Morocco and a literature review, we propose a comparative study of place branding practices between two French regions and the Moroccan Oriental region, in order to define the similarities and differences, in an attempt to outline a marketing practice specific to Moroccan regions.